Comparing Absolute Eosinophil and Monocyte Counts in Critical and Non-Critical COVID-19 Patients: Comparing Eosinophil and Monocyte Counts in COVID-19 Patients - Ishaq, Yasir; Malik, Muhammad Omar; Yousafzai, Yasar Mehmood; Qubtia, Maria; Khan, Imranullah; Mir, Awal (Pakistan Journal of Health Sciences, 2024)
Emerging evidence suggests that variations in immune cell counts, particularly absolute eosinophil and monocyte counts may be important in predicting the clinical course and severity of the disease in COVID-19 patients. Objective: To compare the absolute eosinophil and monocyte counts ‘between critical and non-critical COVID-19 patients to elucidate potential associations with disease severity and prognosis. Methods: Between March 19th and June 6th, 2021, peripheral blood samples were taken from 26 ‘critical COVID-19 patients and 26 non-critical COVID-19 patients. Standard laboratory procedures were used to determine the immunological and haematological parameters for every participant. Whole blood samples were taken in ethylenediaminetetraacetic acid (EDTA) tubes and processed per the manufacturer’s instructions using an automated haematology analyser (XN-1000, Sysmex, Japan). Results: Critical patients of COVID-19 exhibited significantly reduced absolute eosinophil, absolute monocyte, and lymphocyte count compared to non-critical patients. Additionally, critical patients were significantly older. However, there is no significant differences in the two groups’ basophil counts, neutrophil counts, WBC counts, RBC counts, HCT percentage, HGB levels, MCH levels, MCV, MCHC levels, and MPV or platelet counts. Conclusions: Critical patients exhibited significantly reduced absolute eosinophil and monocyte counts suggesting a potentially weaker immune response in these subgroups. The significance of immune cell counts in assessing the severity of COVID-19 is highlighted by these results which may aid in developing targeted therapeutic interventions and prognostic indicators. Validating these results and clarifying their therapeutic significance will require more investigation.